PERENCANAAN STRATEGI PEMASARAN USAHA BENGKEL BARU (STUDI KASUS DI INTI MOTOR PONOROGO) - Kusumo, Stephanie; Surjani, Rosita Meitha; Rinawiyanti, Esti Dwi (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2013)
The addition of the motorcycle population is increasing every year. Thedensity of activity in the streets is demanding comfort, so the vehicle should bealways in good condition. Therefore it’s required that the user do service formotorcycle routinely. INTI MOTOR was established by Mr David Hartanto onDecember 29, 2011 in Jl. K.H. Ahmad Dahlan No. 25 Ponorogo. INTI MOTOR isa business unit that sells a variety of motorcycle spare parts and variations, as wellas serving motorcycle repair service, oil change, replace accu etc. The uniquenessof this workshop which distinguishes it from other workshop is a specialistcleaning services polished motorcycle. For this time being, INTI MOTOR is thefirst workshop in Ponorgo that provides cleaning polishing. However, thissuperiority couldn’t attack costumer. That’s why INTI MOTOR should takeproper planning and marketing strategies in order to be more effectivelyintroducing and stimulating consumer interest towards this superior service whichstill new in the town of Ponorogo. Currently as a new business workshop, thisworkshop’s sale has not still reached the BEP and difficult to gain a profit. So it’snecessary that INTI MOTOR has a marketing planning strategies in order toreach BEP quickly.The study was conducted by distributing questionnaire to the group ofrespondents actual consumers and potential consumers. The results of thequestionnaire was used to plan marketing strategies including STPD:Segmentation based on demographic aspects, the Targetting is the INTIMOTOR’s consumers who have motorcycle, men between 16-35 years old,family status, the occupation is self-employed, with an average expenditureamong <Rp 1,000,000 to Rp 1,999,999 per month, the Positioning is to build theimage with the tagline that could represent INTI MOTOR “harga terjangkauservice memuaskan". INTI MOTOR’s Differentiation is product differentiationwhich is a specialist cleaning polishing motorcycle. Proposed differentiation isprograms and tools to perform injection engine service, tire opener, andmotorcycle lifts. Other marketing strategies are 8P marketing mix which includeElements Product, Place and Time, Price and Other User Outlays, Promotion andEducation, Process, Physical Environment / Evident, People, and Productivity andQuality, the total cost of application of the entire strategy is Rp 27.955.925.